The Effectiveness of Proprioceptive Training in Preventing Re-injury in Football Athletes - Muhammad Ijlal Firdaus; Mohammad Akbar Haidar; Faqih Rozin Ishomi; Evania Yaffa Wardhono; Rizky Patria Nevangga (Journal of Sports Medicine and Physiotherapy, 2025)
Background: Ankle sprain is a common injury among football athletes and is associated with a high recurrence rate. Objectives: . This study explores the effectiveness of proprioceptive training in preventing re-injury through a qualitative phenomenological approach. Methods: This study adopts a qualitative approach with a phenomenological design, aiming to explore the subjective experiences of football athletes regarding the effectiveness of proprioceptive training in preventing recurrent injuries Results: The findings, based on interviews with athlete, indicate that proprioceptive exercises such as single leg stance, balance board training, and small jump drills significantly improve ankle stability, reduce pain, and enhance functional movement. Beyond physical recovery, the training also contributed to improved psychological well-being, particularly by reducing fear of re-injury and restoring confidence during gameplay. This study concludes that proprioceptive training is effective in lowering the risk of recurrent ankle sprain among athletes with previous injury history and plays a crucial role in both physical and mental recovery, supporting optimal return to sport performance. Conclusion: Proprioceptive training is an exercise to train balance and coordination, the better the proprioceptive the possibility of injury will be very small. Proprioceptive training reduces the risk of ankle sprains among sports populations especially in football.